The Impact of Information on Research and Development Activities of Nuclear Scientists in Ghana - Agyeman, E.A.; Kisiedu, Chritine O. (Ghana Library Journal, 2006)
This paper considers the relationship between information use and the professional development of nuclear scientists in Ghana. The assumption is that, frequent use of library and information services results in higher productivity and achievement. Consequently, a national survey of nuclear scientists was conducted using the questionnaire method. The results indicate that information use leads to increase in the volume and quality of work output of nuclear scientists. Evidence is also found to support the claim that information use enhances contributions of scientists to their organizations.